Mine, ours, and yours: Whose engagement and prior knowledge affects individual achievement from online collaborative learning?. (17th June 2020) - Slof, Bert; van Leeuwen, Anouschka; Janssen, Jeroen; Kirschner, Paul A.
Abstract: In computer‐supported collaborative learning research, studies examining the combined effects of individual level, group level and within‐group differences level measures on individual achievement are scarce. The current study addressed this by examining whether individual, group and within‐group differences regarding engagement and prior knowledge predict individual achievement. Engagement was operationalised as group members' exhibited activities in the task space (i.e., discussing domain‐content) and social space (i.e., regulating ideas, actions and socioemotional processes). Prior knowledge and achievement were operationalised as group members' performance on a domain‐related pre‐test and post‐test, respectively. Data was collected for 95 triads of secondary education students collaborating on a complex business‐economics problem. Subsequently, three different multilevel models were tested to examine the combined effect. First a model with the individual level measures (model 1) was tested and in subsequent models the group level measures (model 2) and within‐group levels measures (model 3) were added. Findings indicate model 2 showed the best fit; group members' individual engagement in the social space activities as well as the groups' average prior knowledge positively predicts individual achievement. No effects were found for either group members' or groups' engagement in the task space and for the within‐group differences. Lay Description: Effects of groups, within‐group differences and individuals are often studied separately. Engagement and prior knowledge were related to individual achievement (post‐test). Individual regulatory engagement (shared understanding) positively predicts achievement. Group average prior knowledge (pre‐test score) positively predicts achievement. The effects of within‐group differences remain a topic for future research.